Modulation of Physiological Responses as Indices of Attentional Bias in Dysphoria. - Gantiva, Carlos; Araujo, Andrés; Aragão, Narayana; Hewitt, Nohelia (International Journal of Mental Health & Addiction, 2018)
The experimental results on attentional bias in depression have been contradictory. Research on physiological correlates that validate attentional bias have been scarce. The aim of the present study was to evaluate physiological responses associated with attentional bias in dysphoria. Heart rate and the galvanic skin response were recorded in 30 dysphoric individuals and 30 nondysphoric individuals while they performed an emotional Stroop task. Dysphoric individuals exhibited attentional bias and heart rate deceleration in response to unpleasant words. Nondysphoric individuals exhibited attentional bias toward pleasant words, accompanied by a higher skin conductance response. These results suggest that heart rate deceleration in response to unpleasant words correlated with attentional bias in dysphoric individuals.